'Plug and pipe' strategy for treatment of ruptured intracranial aneurysms. (7th July 2018) - Howard, Brian M; Frerich, Jason M; Madaelil, Thomas P; Dion, Jacques E; Tong, Frank C; Cawley, C Michael; Grossberg, Jonathan A
Abstract : Background: Aneurysmal subarachnoid hemorrhage is a potentially devastating condition, and among the first priorities of treatment is aneurysm occlusion to prevent re-hemorrhage. An emerging strategy to treat patients whose aneurysms are not ideal for surgical or endovascular treatment is subtotal coiling followed by flow diversion in the recovery phase or 'plug and pipe'. However, data regarding the safety and efficacy of this strategy are lacking. Methods: A retrospective cohort study was performed to evaluate the efficacy and safety of 'plug and pipe'. All patients with a ruptured intracranial aneurysm intentionally, subtotally treated by coiling in the acute stage followed by flow diversion after recovery, were included. The primary outcome was re-hemorrhage. Secondary outcomes included aneurysm occlusion and functional status. Complications were reviewed. Results: 22 patients were included. No patient suffered a re-hemorrhage, either in the interval between coiling and flow diversion or in follow-up. The median interval between aneurysm rupture and flow diversion was 3.5 months. Roy–Raymond (R-R) class I or II occlusion was achieved in 91% of target aneurysms at the last imaging follow-up (15/22(68%) R-R 1 and 5/22(23%) R-R 2). Complications occurred in 2 (9%) patients, 1 of which was neurological. Conclusions: Overall, these data suggest that subtotal coiling of ruptured intracranial aneurysms followed by planned flow diversion is both safe and effective. Patients who may most benefit from 'plug and pipe' are those with aneurysms that confer high operative risk and those whose severity of medical illness increases the risk of microsurgical clip ligation.